Modified Balloon Protection Technique for Preoperative Embolization of Feeder Arteries from Internal Carotid Artery Branches to Skull-Base Tumor: Technical Note - Adachi, Kazuhide; Hayakawa, Motoharu; Sadato, Akiyo; Hayashi, Takuro; Maeda, Shingo; Nagahisa, Shinya; Hasegawa, Mitsuhiro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective To improve bleeding management during brain tumor surgery, feeder arteries supplying the tumor are often embolized presurgically. However, access to feeder arteries can be limited, and embolization of feeders from internal carotid artery (ICA) branches often causes complications. We evaluated the PercuSurge GuardWire (Medtronic, Minneapolis, Minnesota, United States) system (PGWS) with aspiration catheter as a modification of the embolization technique used to block tumor-supplying branches of the ICA.Methods Two skull-base tumors were treated with preoperative embolization. One was a meningioma; the other was a hemangiopericytoma. In each case, the microcatheter could not be threaded into the ICA feeder arteries. Therefore, particulate embolic material was injected near the ICA branch while maintaining ICA balloon protection by the PGWS at the orifice of the ophthalmic artery. After embolization, we removed the remaining embolic material in the ICA using an aspiration catheter. In both cases, there were no postembolization complications and no high-intensity areas in the diffusion-weighted magnetic resonance image, and the tumorectomy proceeded as scheduled.Conclusion This modified technique may be a promising alternative for reducing embolic complications and improving the success rate, although case accumulation is needed to confirm this result.
Keywords: internal carotid artery; preoperative embolization; skull-base tumor